Music and Cognitive Extension - Kersten, Luke (Empirical Musicology Review, 2015)
Extended cognition holds that cognitive processes sometimes leak into the world (Dawson, 2013). A recent trend among proponents of extended cognition has been to put pressure on phenomena thought to be safe havens for internalists (Sneddon, 2011; Wilson, 2010; Wilson & Lenart, 2014). This paper attempts to continue this trend. It is argued that because music perception is as part of a locationally wide computational system, it is an extended process. In articulating the view, the work of J.J Gibson (1966, 1986) and Robert Wilson (1994b, 1995, 2004) is drawn on. The view is defended from objections and its implications outlined. The paper concludes with a comparison to Krueger’s (2014) view of the “musically extended emotional mind”.